FORMATION OF POSITIVE ATTITUDE TO PHYSICAL EDUCATION LESSONS FOR SCHOOLCHILDREN THROUGH THE EDUCATION OF THE MODERN TEACHER - Andrianov, T.V.; Marchyk, V.I.; Andrianov, V.E. (Pedagogy of Higher and Secondary Education, 2004)
It Is Determined that actions, which effectively raise the interest a pupil to physical culture, are found in border professional strong, bright, enthusiastic personality - a teacher of the physical culture, which actively propagandizes the ideas of the physical culture and sport.